A case of advanced-stage endometrial stromal sarcoma of the ovary arising from endometriosis - Back, Ju A; Choi, Myeong Gyune; Ju, U Chul; Kang, Woo Dae; Kim, Seok Mo (Obstetrics & gynecology science, 2016)
Endometrial stromal sarcoma (ESS) is a rare malignancy. Development of extrauterine ESS form endometriosis is particularly rare. The majority of extrauterine ESS occurs in areas with preexisting endometriosis. The most common site is the ovary. We experienced a case of ESS of the ovary that arose from endometriosis with multiple disseminated lesions. This disease was managed by total abdominal hysterectomy, bilateral salpingo-oophorectomy, both pelvic lymph nodes dissection, omentectomy, and appendectomy followed by postoperative high-dose progesterone therapy. Here, we report this case with literature review.